2017
DOI: 10.1111/pcn.12621
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms of major depression: Targeting neuronal plasticity

Abstract: Major depressive disorder is one of the most common mental illnesses as it affects more than 350 million people globally. Major depressive disorder is etiologically complex and disabling. Genetic factors play a role in the etiology of major depression. However, identical twin studies have shown high rates of discordance, indicating non‐genetic mechanisms as well. For instance, stressful life events increase the risk of depression. Environmental stressors also induce stable changes in gene expression within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 174 publications
(395 reference statements)
1
88
0
2
Order By: Relevance
“…Recent studies suggest that the beneficial effect of antidepressant drugs is mediated via stimulation of adult hippocampal neurogenesis and subsequent increase in hippocampal plasticity. Changes in hippocampal neurons can play an important role in the pathogenesis of depression, involving the possible mechanism of ERK (extracellular signal-regulated kinase) pathway [7], AMPK (Adenosine monophosphate-activated protein kinase) pathway [8], GABAergic dysfunction in the nucleus accumbens (NAc) [9], epigenetic events altering the chromatin structure and thus modulating expression of genes [10], Sirt1 (silent information regulator 1) at the consumption of NAD+ [11], BDNF pathway [12,13], etc. However, mitochondrial energy metabolism in depression remains poorly understood although the action of the above mentioned signalings, at least in part, relies on energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that the beneficial effect of antidepressant drugs is mediated via stimulation of adult hippocampal neurogenesis and subsequent increase in hippocampal plasticity. Changes in hippocampal neurons can play an important role in the pathogenesis of depression, involving the possible mechanism of ERK (extracellular signal-regulated kinase) pathway [7], AMPK (Adenosine monophosphate-activated protein kinase) pathway [8], GABAergic dysfunction in the nucleus accumbens (NAc) [9], epigenetic events altering the chromatin structure and thus modulating expression of genes [10], Sirt1 (silent information regulator 1) at the consumption of NAD+ [11], BDNF pathway [12,13], etc. However, mitochondrial energy metabolism in depression remains poorly understood although the action of the above mentioned signalings, at least in part, relies on energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Also, symptoms of depression are present in a significant proportion of Alzheimer’s disease patients (Cerejeira et al, 2012). While, pathophysiology of depression remains poorly understood, aberrant epigenetic regulation of gene transcription has been suggested in patients with major depression as well as in animal models of depression (Consortium, 2015; Robison and Nestler, 2011; Sun et al, 2013; Uchida et al, 2017b). Several of the activity-dependent transcription factors and cofactors have been associated with depression, including CREB (Carlezon et al, 2005), MeCP2 (Hutchinson et al, 2012; Uchida et al, 2011) and CRTC1 (Meylan et al, 2016a; Meylan et al, 2016b).…”
Section: Possible Involvement Of Crtc1 and Fgf1 In Memory-related Dismentioning
confidence: 99%
“…Despite the physiopathological mechanism of depression remaining not widely elucidated and unclear, numerous studies have shown a multifactorial origin, involving genetics, environmental, psychological, and social factors, as well as dysfunction in multiple brain areas such as the hippocampus, prefrontal cortex, nucleus accumbens, and amygdale [7][8][9][10]. Recent findings of the presence of inflammatory process and oxidative stress in the pathophysiology of depression provide new pathways and treatment targets for improvement of pharmacological approach in depression [11].…”
Section: Introductionmentioning
confidence: 99%